Design and dimensioning of an edge router using Markov model. (29th June 2009) - Bhattacharjee, Partha; Sanyal, Goutam
This paper presents the formulation, modelling and analysis of network traffic for the purpose of designing an edge router. Presuming packet arrival in Poisson's process and departure or service time distribution to be exponential, a Markov model has been developed. The stochastic characteristics of the traffic has been monitored and studied over long durations. Traffic data was captured from internet backbone. Different design parameters like buffer capacity, outgoing link speed and various other key parameters have been derived. Additionally, an algorithm has been suggested to manipulate the weights of the queues dynamically in a weighted round robin scheduling, thereby changing the packet departure rate of the flows. The algorithm eventually provides a control over the load factors and the probability of packet drop of the flows as per the need of quality of service and differentiated service.